Human resource redeployability and entrepreneurial hiring strategy - Hietaniemi, Liinus; Santamaria, Simone; Kacperczyk, Aleksandra; Peltonen, Juhana (Strategic Management Journal, 2024)
Research Summary The timing of talent acquisition is a central decision for new ventures. On one hand, hiring after demand is proven minimizes losses. On the other hand, hiring before demand is proven allows new ventures to start developing unique capabilities. We resolve this tension by proposing that the timing depends on human resource redeployability. We test our theory with the population of Finnish ventures showing that portfolio entrepreneurs hire more employees early on because of higher redeployment potential and that they hire employees with more transferable skills in order to benefit from the redeployment option. To probe our mechanisms, we examine how talent acquisition strategies in portfolio and standalone ventures vary with external conditions that reduce or amplify the benefits of redeployment. Managerial Summary This paper explores when startups begin scaling their team. Our findings suggest that the potential to redeploy employees (to another startup, for example) motivates entrepreneurs to scale earlier. At the same time, we find that the entrepreneurs who scale earlier due to redeployment potential tend to hire employees with skills that can be transferred more easily. We further show that our results are affected by the level of rigidity in the labor market. When labor markets become more flexible, the impact of easy redeployment on an entrepreneur's hiring strategy becomes less important. Our findings provide important insights into how the external environment and policy changes can affect the trajectory of startups even at their earliest stages.